Modified Iron Oxide Magnetic Nanosheets With Nitrogen-Containing Functional Groups as Chloridazon Adsorbent - Marzieh Piryaei; Mehdi Abolghasemi; Sayna Jodatvand (Nanochemistry Research)
Mesostructured iron oxide/ethylene glycol (FeOx/EG) nanosheets with an oval shape were created and employed as a magnetic solid-phase extraction (MSPE) sorbent to extract herbicide chloridazon. Iron oxide layers are intercalated with deprotonated ethylene glycol molecules to provide an interlayer gap of 10.6 A. Using scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), thermal gravimetric analysis (TGA), and a vibrating sample magnetometer (VSM), the size, shape, content, and characteristics of the produced nanocomposite were determined. The key influencing factors for extracting chloridazon, such as the volume of the sample, the amount of sorbent, and the desorption solvent, were optimized. High-performance liquid chromatography with UV detection was the subject of analyses. The approach demonstrated strong linearity in the range of 0.01–100 µg.mL-1, reasonable repeatability (RSD 3.017%, n = 3), and limits of detection (0.001 µg.mL-1) under the ideal extraction conditions.